Containment of COVID-19: the unprecedented response of Saudi Arabia - Dalia A Obied; Fatimah S Alhamlan; Ahmed A Al-Qahtani; Mohammed N Al-Ahdal (Journal of Infection in Developing Countries)
The emergence of a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), from Wuhan, China, in December 2019 has challenged many countries. The current pandemic caused by this coronavirus has already negatively affected millions of people and the economies of countries worldwide. However, the challenges faced by Saudi Arabia during the Middle East respiratory syndrome coronavirus (MERS-CoV) epidemic that began in 2012 led to marked improvements in the government’s response to the current pandemic. Saudi Arabia is one of largest countries in the Middle East and is home to the holiest Muslim sites. Since the global risk of the virus was declared by the World Health Organization (WHO), Saudi Arabia has taken substantial public health measures to control the spread of the infection. This review reports on the transmission of SARS-COV-2 in Saudi Arabia and the proactive responses taken by the government, comparing the Saudi government’s actions and their effects with those of other countries. Although Saudi Arabia is currently experiencing the peak of the pandemic, their early precautionary responses have shortened the period of individual/family isolation, reduced the number of confirmed infections and infection-related fatality rates, and decreased the economic burden of the people and the country compared with other countries in the Middle East and elsewhere.